"The Living Monument": The Desegregation of Grady Memorial Hospital and the Changing South. Issue 3 (March 2020) - Lovasik, Brendan P.; Rajdev, Priya R.; Kim, Steven C.; Srinivasan, Jahnavi K.; Ingram, Walter L.; Sayed, Blayne A.
Grady Memorial Hospital is a pillar of public medical and surgical care in the Southeast. The evolution of this institution, both in its physical structure as well as its approach to patient care, mirrors the cultural and social changes that have occurred in the American South. Grady Memorial Hospital opened its doors in 1892 built in the heart of Atlanta's black community. With its separate and unequal facilities and services for black and white patients, the concept of "the Gradies" was born. Virtually, every aspect of care at Grady continued to be segregated by race until the mid-20th century. In 1958, the opening of the "New Grady" further cemented this legacy of the separate "Gradies, " with patients segregated by hospital wing. By the 1960s, civil rights activists brought change to Atlanta. The Atlanta Student Movement, with the support of Dr. Martin Luther King Jr., led protests outside of Grady, and a series of judicial and legislative rulings integrated medical boards and public hospitals. Eventually, the desegregation of Grady occurred with a quiet memo that belied years of struggle: on June 1, 1965, a memo from hospital superintendent Bill Pinkston read "All phases of the hospital are on a non-racial basis, effective today." The future of Grady is deeply rooted in its past, and Grady's mission is unchanged from its inception in 1892: "It will nurse the poor and rich alike and will be an asylum for black and white."